PENGARUH PERMAINAN EDUKATIF DENGAN MEDIA PUZZLE TERHADAP PERKEMBANGAN KOGNITIF DALAM MENGENAL BENTUK DAN WARNA PADA ANAK PRASEKOLAH DI TK AISYIYAH IV KOTA JAMBI - Rahima Rahima (Jurnal Akademika Baiturrahim Jambi, 2017)
Bacgroud : Growth and development of early childhood requires a variety of stimulus because at that age is a very important time for children to develop in accordance with their needs and potential. According to the Indonesian Pediatricians Association (IDAI) conduct examination in the age range 0-6 years. The results obtained that 69.4% of children can not achieve the development of cognitive function, language and speech.Method : This research is a pre experiment research with one group pretest-posttest design. A sample of 15 children with purposive sampling technique on August 27 to June 05, 2017. Data analysis used is Univariat and Bivariat with t-test with 95% confidence level and α: 5%. The results showed that there was an influence of educational game with puzzle media on cognitive development in recognizing the shape and color of preschoolers (4-5,5 years) with p-value = 0,000 <0.05. Result The conclusion of this research is that statistically there is influence of educative game with media puzzle to cognitive development in recognizing the shape and color of preschool age children (4-5,5 year).For that, it is expected to effectively improve the cognitive development in children.